Decarbonizing Europe's power sector by 2050 - Analyzing the implications of alternative decarbonization pathways - Cosima Jägemann; Michaela Fürsch; Simeon Hagspiel; Stephan Nagl (Institute of Energy Economics at the University of Cologne (EWI), 2012)
In this paper, the implications of alternative decarbonization pathways for Europe's power sector up until the year 2050 are analyzed. In speci fic, an electricity system optimization model is used to investigate the minimal costs of decarbonization under a stand-alone CO2 reduction target and to quantify the excess costs associated with renewable energy targets and politically implemented restrictions on alternative lowcarbon technologies, such as nuclear power. Our numerical simulations con firm the theoretical argumentation concerning counterproductive overlapping regulation. The decarbonization of Europe's power sector is found to be achieved at minimal costs under a stand-alone CO2 reduction target (171 bn exteuro2010). Additionally implemented RES-E targets lead to signi cant excess costs of at least 237 bn exteuro2010. Excess costs of a complete nuclear phase-out in Europe by 2050 are of the same order of magnitude (274 bn exteuro2010).
Keywords: C61; Q40; Q50; 330; Electricity; CO2 target; renewable target; excess costs; optimization model